الإعتماد المستندي و دوره في تنظيم التجارة الخارجية - أمال, خرفي; أيمن, بكوشة; فراس, بلعروسي; ميسون, شراديد (جامعة الوادي - University of Eloued, 2023)
تحتاج المؤسسات على أموال من أجل تلبية احتياجاتها حيث قد تكون هذه الاحتجاجات عند نشأة المؤسسة أو عند تجديد وسائل أو معدات للقيام بمشاريع اقتصادية وتطويرها ذلك عن طريق أساليب التمويل الحديثة التقليدية مم وتعد التجارة الخارجية من القطاعات الحيوية في مجتمع اقتصادي سواء كان ذلك المجتمع متقدم أو متأخر فالتجارة الخارجية تربط الدول و المجتمعات مع بعضها البعض ونظرا لزيادة المعاملات الدولية من ازدادت الحاجة على التمويل التجاري الخارجية وتلعب البنوك بأنواعها دورا أساسي في تطور الاقتصاد الوطني ويعتمد كذلك على تسوية المعلمات على انواع شتى من الندوات والميكانيزمات منها التسوية نقدا والتحويلات عن طريق السويفت و يعتبر او الاعتماد المستندي أحد وسائل الدفع الهامة و لمتطورة التي يمكن من خلالها تمويل التبادل باعتباره وسيلة الدفع على النطاق الخارجي بقدرته على التغلب على العديد من المشاكل المرتبطة بالتبادل التجاري. Institutions need funds in order to meet their needs, as these protests may be at the establishment of the institution or when renewing means or equipment to carry out economic projects and develop them through traditional modern financing methods. Foreign trade is one of the vital sectors in an economic society, whether that society is advanced or late. Foreign trade links countries and societies with each other, and due to the increase in international transactions, the need for foreign trade financing has increased. Banks of all kinds play a fundamental role in the development of the national economy, and it also depends on the settlement of parameters on various types of seminars and mechanisms, including cash settlement and transfers via Swift, and it is considered or Documentary credit is one of the important and developed means of payment through which exchange can be financed as a means of payment on the external scale with its ability to overcome many problems associated with commercial exchange.
Keywords: الإعتماد المستندي /التجارة الخارجية/بنك القرض الشعبي الجزائري; Credit documentaiire/commerce international/cpa credit algeriene du poulaire